Influence of neprilysin inhibition on the efficacy and safety of empagliflozin in patients with chronic heart failure and a reduced ejection fraction: the EMPEROR-Reduced trial - Packer, Milton; Anker, Stefan D; Butler, Javed; Filippatos, Gerasimos; Ferreira, Joao Pedro; Pocock, Stuart J; Rocca, Hans-Peter Brunner-La; Janssens, Stefan; Tsutsui, Hiroyuki; Zhang, Jian; Brückmann, Martina; Jamal, Waheed; et al. (European heart journal, 2021)
We evaluated the influence of sacubitril/valsartan on the effects of sodium-glucose cotransporter 2 (SGLT2) inhibition with empagliflozin in patients with heart failure and a reduced ejection fraction.The EMPEROR-Reduced trial randomized 3730 patients with heart failure and an ejection fraction ≤40% to placebo or empagliflozin (10 mg/day), in addition to recommended treatment for heart failure, for a median of 16 months. A total of 727 patients (19.5%) received sacubitril/valsartan at baseline. Analysis of the effect of neprilysin inhibition was 1 of 12 pre-specified subgroups. Patients receiving a neprilysin inhibitor were particularly well-treated, as evidenced by lower systolic pressures, heart rates, N-terminal prohormone B-type natriuretic peptide, and greater use of cardiac devices (all P < 0.001) when compared with those not receiving sacubitril/valsartan. Nevertheless, when compared with placebo, empagliflozin reduced the risk of cardiovascular death or hospitalization for heart failure in patients receiving or not receiving sacubitril/valsartan [hazard ratio 0.64 (95% CI 0.45-0.89), P = 0.009 and hazard ratio 0.77 (95% CI 0.66-0.90), P = 0.0008, respectively, interaction P = 0.31]. Empagliflozin slowed the rate of decline in estimated glomerular filtration rate by 1.92 ± 0.80 mL/min/1.73 m2/year in patients taking a neprilysin inhibitor (P = 0.016) and by 1.71 ± 0.35 mL/min/1.73 m2/year in patients not taking a neprilysin inhibitor (P < 0.0001), interaction P = 0.81. Combined inhibition of SGLT2 and neprilysin was well-tolerated.The effects on empagliflozin to reduce the risk of heart failure and renal events are not diminished in intensively treated patients who are receiving sacubitril/valsartan. Combined treatment with both SGLT2 and neprilysin inhibitors can be expected to yield substantial additional benefits.
Gesehen am 31.05.2021